Effect of water bath temperature on physiological parameters and subjective sensation in older people. Issue 11 (19th April 2017) - Ono, Junji; Hashiguchi, Nobuko; Sawatari, Hiroyuki; Ohkusa, Tomoko; Miyazono, Mami; Son, Su‐young; Magota, Chie; Tochihara, Yutaka; Chishaki, Akiko
Abstract: Aim: In Japan, the incidence of water bathing‐related cardiopulmonary accidents among older people is high in winter. The purpose of the present study was to investigate alterations in physiological characteristics and subjective thermal sensations of older people when bathing in a cool environment. Methods: We assessed the skin temperature, rectal temperature, blood pressure, pulse rate, body fluid loss (sweat and urine), and subjective thermal responses of 11 older healthy male and 10 young male volunteers throughout 42°C and 39°C bathing in a room at 20°C with 50% humidity. Results: At 42°C bathing, the rectal temperature during bathing and in the post‐bathing period were significantly lower in the older men than in the young men, and skin temperature during the post‐bathing period decreased gradually in the older men. Systolic blood pressure and pulse rate immediately increased just after entering 42°C water and decreased during bathing in the older men. With the activities of dressing, systolic blood pressure increased followed by a decrease during the post‐bathing period. Thus, double product (pulse rate × systolic blood pressure) increased during the bathing period. Although there was no significant difference in body fluid loss between the older and younger men in 42°C water, the older men produced significantly less sweat. The older men also reported feeling less warm after 42°C bathing, and feeling less cold during the post‐bathing period after 39°C bathing. Conclusions: These results suggest that hot water bathing during cold seasons might induce more serious physiological changes in older people.Geriatr Gerontol Int 2017; 17: 2164–2170 .